2018
DOI: 10.15561/18189172.2018.0602
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the functional characteristics and motor qualities of students of different generations and body types

Abstract: Purpose : the comparative analysis of screening studies of physical fitness and functional condition of young men with different body types (the territory of Baikal region, Russia; the interval of the study is 10 years). Material : First-year students (age 17-18 years; n = 1003; in 2008 - n = 523; in 2017 - n = 480) of Irkutsk National Research Technical University (Pribaikalye, Russia) participated into the research. All students are classified for health reasons to the main medical group (no deviations in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Other studies show the correlations between physical development and physical fitness of youth. It was confirmed the high significance of body mass index and thickness of skin and fat folds for predicting the condition of youth with different body types (Agata & Monyeki, 2018;Kolokoltsev, Iermakov, & Jagiello, 2018).…”
Section: Introductionmentioning
confidence: 57%
“…Other studies show the correlations between physical development and physical fitness of youth. It was confirmed the high significance of body mass index and thickness of skin and fat folds for predicting the condition of youth with different body types (Agata & Monyeki, 2018;Kolokoltsev, Iermakov, & Jagiello, 2018).…”
Section: Introductionmentioning
confidence: 57%
“…The analysis of the results of experimental work showed that the methodical system of fitness technologies application in the educational process on physical education of students in higher pedagogical education establishments contributes to the education of a positive attitude of students to the means of physical culture and sports, improves motor and physical activity of students. According to scientists [6,16,25,26,27], motor activity consists of movements that are one of the necessary conditions of life. It improves work capability, health, provides versatile harmonious development, functioning of the cardiovascular, respiratory, hormonal and other systems of the body, activates the neuromuscular apparatus and mechanisms for transferring the reflexes from the muscles to the internal organs.…”
Section: Resultsmentioning
confidence: 99%
“…The level of physical fitness is an important factor in job satisfaction for the police officers involved in critical incidents and to perform tasks with significant physical activity. The importance of this confirmation is emphasized in studies devoted to the influence of significant physical activity in sports (Podrigalo, Galashko, Iermakov, Rovnaya & Bulashev, 2017), physical culture (Kolokoltsev, Iermakov, & Jagiello, 2018), in military officers training (Anatskyi, Kolomiitseva, Cretu & Potop, 2017).…”
Section: Discussionmentioning
confidence: 95%